Posterior Reversible Encephalopathy Syndrome in a Patient with Newly Diagnosed HIV Infection and End Stage Renal Disease - Mohankumar Kurukumbi; Maria I. Castellanos; Amanda K. Crawford; Shreyas D. Gowdar; Annapurni Jayam-Trouth (Case Reports in Neurological Medicine)
Posterior reversible encephalopathy syndrome (PRES) is a clinicoradiological syndrome in which patients present with an acute or subacute clinical presentation of seizures, visual disturbances, headache, and altered mental status. The pathophysiology of PRES may be explained by endothelial dysfunction that leads to transudation of fluids and protein, resulting in vasogenic cerebral edema. PRES is typically associated with many conditions such as hypertension, uremia, immunosuppressive drugs, and sepsis. This is a case report of a 39-year-old woman with untreated HIV infection and end-stage renal disease (ESRD) who developed PRES with a normal blood pressure and no other known causes of PRES. Untreated HIV is associated with known endothelial dysfunction and we believe that this, in combination with her untreated end-stage renal disease, contributed to her unique presentation of PRES. Although uncommon in HIV-infected patients and challenging to diagnose, prompt recognition of PRES is critical to provide appropriate care and ensure reversibility of the vasogenic edema seen in PRES.